2020
DOI: 10.1186/s41065-020-00160-y
|View full text |Cite
|
Sign up to set email alerts
|

The homeodomain transcription factor Orthopedia is involved in development of the Drosophila hindgut

Abstract: Background The Drosophila hindgut is commonly used model for studying various aspects of organogenesis like primordium establishment, further specification, patterning, and morphogenesis. During embryonic development of Drosophila, many transcriptional activators are involved in the formation of the hindgut. The transcription factor Orthopedia (Otp), a member of the 57B homeobox gene cluster, is expressed in the hindgut and nervous system of developing Drosophila embryos, but due to the lack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 74 publications
0
20
0
Order By: Relevance
“…Several transcription factors were identified that are important for the proliferation of type I and type II neuroblasts in the brain, leading to an expansion of the brain region compared with the ventral nerve cord [ 17 ]. They include Earmuff (Erm), belonging to the FEZ family of C2H2 Zinc finger transcription factors [ 18 ], Tailless (Tll), a nuclear receptor transcription factor [ 19 ], the T-box transcription factors Doc1/2/3 [ 20 ] as well as the three homeodomain transcription factors Orthopedia (Otp) [ 21 , 22 ], Drosophila Retinal homeobox (DRx) [ 23 , 24 ] and Homeobrain (Hbn) [ 25 , 26 ], clustered in the 57B region on the second chromosome. Mutants of all these factors alone or in combination show a reduction of neuroblasts and the proliferation of their daughter cells in the embryonic brain.…”
Section: Introductionmentioning
confidence: 99%
“…Several transcription factors were identified that are important for the proliferation of type I and type II neuroblasts in the brain, leading to an expansion of the brain region compared with the ventral nerve cord [ 17 ]. They include Earmuff (Erm), belonging to the FEZ family of C2H2 Zinc finger transcription factors [ 18 ], Tailless (Tll), a nuclear receptor transcription factor [ 19 ], the T-box transcription factors Doc1/2/3 [ 20 ] as well as the three homeodomain transcription factors Orthopedia (Otp) [ 21 , 22 ], Drosophila Retinal homeobox (DRx) [ 23 , 24 ] and Homeobrain (Hbn) [ 25 , 26 ], clustered in the 57B region on the second chromosome. Mutants of all these factors alone or in combination show a reduction of neuroblasts and the proliferation of their daughter cells in the embryonic brain.…”
Section: Introductionmentioning
confidence: 99%
“…The Drosophila orthopedia (otp) gene codes for a homeodomain transcription factor (Simeone et al, 1994;Hildebrandt et al, 2020) and is a member of the 57B homeobox gene cluster together with Drosophila Retinal homeobox (DRx) (Eggert et al, 1998;Davis et al, 2003) and homeobrain (hbn) (Walldorf et al, 2000;Kolb et al, 2021). All three transcription factors are expressed in type I and type II neuroblasts in the brain and are important for progenitor cell proliferation leading to an expansion of the brain region compared with the ventral nerve cord (Curt et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In vertebrates orthologs have been identified in zebrafish (Del Giacco et al, 2008), chicken (Simeone et al, 1994;Caqueret et al, 2005), mouse (Simeone et al, 1994) and human (Lin et al, 1999). In the Drosophila embryo Otp is expressed in the nervous system and the hindgut, and otp mutant alleles show a severe hindgut phenotype with a complete loss of the large intestine and a reduction of the anal pads (Hildebrandt et al, 2020). This hindgut phenotype, which is due to apoptosis in the developing hindgut, leads to embryonic lethality of otp mutant alleles (Hildebrandt et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it was shown that DRx is also one of several transcription factors that are expressed in type II neuroblasts in the embryonic brain and important for progenitor cell proliferation leading to an expansion of the brain region compared with the ventral nerve cord [ 39 ]. Homeodomain transcription factors such as Orthopedia (Otp) [ 40 , 41 ] and Homeobrain (Hbn) [ 42 , 43 ] belong to these factors and are together with DRx encoded next to each other in the 57B region on the second chromosome [ 42 ]. Mutants of all these factors alone or in combination show a reduction in neuroblasts and the proliferation of their daughter cells.…”
Section: Introductionmentioning
confidence: 99%